Dietary acrylamide intake during pregnancy and postnatal growth and obesity: Results from the Norwegian Mother and Child Cohort Study (MoBa). (April 2018) - Kadawathagedara, Manik; Botton, Jérémie; de Lauzon-Guillain, Blandine; Meltzer, Helle Margrete; Alexander, Jan; Brantsaeter, Anne Lise; Haugen, Margaretha; Papadopoulou, Eleni
Abstract: Background: Prenatal acrylamide exposure has been negatively associated with fetal growth but the association with child growth is unknown. Objectives: We studied the association between prenatal acrylamide exposure and child postnatal growth up to 8 years in the Norwegian Mother and Child Cohort Study (MoBa). Methods: In 51, 952 mother-child pairs from MoBa, acrylamide intake during pregnancy was estimated by combining maternal food intake with food concentrations of acrylamide. Mothers reported their child's weight and length/height up to 11 times between 6 weeks and 8 years. Weight and height growth trajectories were modelled using Jenss-Bayley's growth model. Logistic regression models were used to study the association with overweight/obese status at 3, 5 and 8 years, as identified using the International Obesity Task Force cut-offs. Linear mixed-effect models were used to explore associations with overall growth. Results: At 3 years, the adjusted odds ratios (95% Confidence Intervals (CI)) of being overweight/obese were 1.10 (1.02, 1.20), 1.12 (1.04, 1.22) and 1.21 (1.11, 1.31) by increasing prenatal acrylamide exposure quartile. Similar dose-response associations were found at 5 and 8 years. Acrylamide intake during pregnancy was associated with higher weight growth velocity in childhood. Children exposed at the highest level had 22 g (95% CI: 8, 37), 57 g (95% CI: 32, 81), and 194 g (95% CI: 110, 278) higher weight at 0.5, 2, and 8 years, respectively, compared to their low exposed peers. Conclusions: Children prenatally exposed to acrylamide in the highest quartile experienced a moderate increase in weight growth velocity during early childhood that resulted in a moderately increased prevalence of overweight/obesity compared to peers in the lowest quartile. Our study is the first to link prenatal acrylamide exposure and postnatal growth. Highlights: Prenatal dietary acrylamide exposure was assessed combining FFQ and contamination data. Prenatally exposed children were more likely to be overweight or obese. Prenatally exposed children were more likely to have higher weight growth velocity. First study on prenatal dietary exposure and postnatal growth that need replication